Kesejahteraan Psikologis pada Lansia Aktif Bekerja: Perspektif Psikologi Positif - Vivi Juli Pratiwi; Furqon Efendi; Febby Fariska (Journal of Medical Practice and Research, 2025)
Psychological well-being includes positive social interactions, physical and mental health, and self-acceptance. This study aims to determine the psychological well-being of elderly people who are still working. The research method used a qualitative approach with a case study type. The research subjects consisted of two elderly people aged 60 years and above who were still actively working. Data were collected through observation and open interviews, while the research location was on Jl. Beringin, Ngaliyan, Semarang, Central Java. The results showed that work activities contributed positively to the psychological well-being of the elderly. Both subjects were able to demonstrate self-acceptance, had clear life goals, and were able to adapt to their surroundings. In addition, they were able to evaluate their past experiences to prepare themselves for a better life in their old age. Working not only provides economic benefits, but also supports self-confidence, independence, and healthy social relationships. Thus, working in old age plays an important role in maintaining psychological well-being, both mentally and socially, thereby improving the overall quality of life of the elderly.